RELATIONSHIP BETWEEN ORAL HEALTH-RELATED QUALITY OF LIFE AND SALIVARY CORTISOL LEVELS IN CHILDREN WITH CARIES - Khairani, Annisa; Fauziah, Eva; Budiardjo, Sarworini B. (International Journal of Applied Pharmaceutics, 2018)
Objective: Dental caries can cause pain and discomfort, especially in children. If they remain untreated, they can impact a child's oral health-related quality of life (OHRQoL) and trigger the release of salivary cortisol. Many research studies have been conducted to determine the influence of dental caries on the OHRQoL and salivary cortisol levels, but none has described the correlation between them. This research examined the correlation between the OHRQoL and the salivary cortisol levels in children with caries. Methods: This experiment was observational and analytical with a cross-sectional design. The experimental data were statistically analyzed using the Kendall's tau and Spearman's rank correlations to compare the OHRQoL and salivary cortisol levels. Results: The results of this study showed that there was a small correlation (r=0.3) between the OHRQoL and salivary cortisol level with a negative trend. This suggests that if the cortisol level slow, the child's OHRQoL is high. The chronic inflammation caused by dental caries can influence the OHRQoL and trigger the release of cortisol in the saliva. Conclusion: Children with good OHRQoLs have low salivary cortisol levels, suggesting an unstressed condition. Practical implications: Untreated caries may cause pulpitis (represent in decayed, missing, and filled teeth in this study) in children aged 8–10 years old has an impact in their OHRQoL. Meanwhile, salivary cortisol levels as biomarker of inflammation may influence in many factors.